Enhanced Public Defense Improves Pretrial Outcomes and Reduces Racial Disparities - Heaton, Paul (2021)
Numerous jurisdictions are working to reform pretrial processes to reduce or eliminate money bail and decrease pretrial detention. Although reforms such as the abandonment of bail schedules or adoption of actuarial risk assessment tools have been widely enacted, the role of defense counsel in the pretrial process has received less attention. This Article considers an approach to pretrial reform focused on improving the quality of defense counsel. In Philadelphia, a substantial fraction of people facing criminal charges are detained following rapid preliminary hearings where initial release conditions are set by bail magistrates operating with limited information. Beginning in 2017, the Defender Association of Philadelphia implemented a pilot program wherein “bail advocates” interviewed defendants shortly after arrest to collect individualized information that could be used to more effectively argue for pretrial release. Using administrative data covering nearly 100,000 criminal cases and a quasi-experimental research design that exploits the random shuffling of arraignment shifts covered by advocates during the pilot, we measure the causal impacts of the advocates on pretrial release, failure to appear, case outcomes, and future crime. Bail advocates did not reduce detention rates (at least on average) but did substantially reduce clients’ likelihood of bail violation (-64%) and future arrest (- 26%). Bail advocates also reduce racial disparities in pretrial detention. Interviews with prosecutors, defenders, and bail advocates suggest that these impacts likely represent both better understanding of defendant risk and needs by magistrates and a better sense of procedural justice by defendants. These results suggest that bail advocates might achieve a key objective desired by proponents of risk assessment tools—the provision of better information to pretrial decisionmakers—without triggering comparable concerns. A workable solution to the problem of improving pretrial outcomes may lie with an old mainstay of the criminal process—the defense attorney